Systematic review and meta-analysis of risk of gestational diabetes in women with preconception mental disorders. (May 2022) - Wilson, Claire A.; Newham, James; Rankin, Judith; Ismail, Khalida; Simonoff, Emily; Reynolds, Rebecca M.; Stoll, Nkasi; Howard, Louise M.
Abstract: There is a well-established bidirectional association between Type 2 diabetes and mental disorder and emerging evidence for an increased risk of perinatal mental disorder in women with gestational diabetes (GDM). However, the relation between mental disorder prior to pregnancy and subsequent risk of GDM remains relatively unexplored. This is a systematic review and meta-analysis of the risk of GDM in women with a range of preconception mental disorders. Peer-reviewed literature measuring odds of GDM and preconception mood, anxiety, psychotic and eating disorders was systematically reviewed. Risk of bias was assessed using a checklist. Two independent reviewers were involved. 22 observational studies met inclusion criteria; most were retrospective cohorts from English speaking, high income countries. 14 studies were at high risk of bias. There was evidence for an increased risk of GDM in women with schizophrenia (pooled OR 2.44; 95% CI 1.17, 5.1; 5 studies) and a reduced risk of GDM in women with anorexia nervosa (pooled OR 0.63; 95% CI 0.49, 0.80; 5 studies). There was some limited evidence of an increased risk in women with bipolar disorder. There was no evidence for an association with preconception depression or bulimia nervosa on meta-analysis. There were insufficient studies on anxiety disorders for meta-analysis. This review indicates that there is not a significant risk of GDM associated with many preconception mental disorders but women with psychotic disorders represent a group uniquely vulnerable to GDM. Early detection and management of GDM could improve physical and mental health outcomes for these women and their children. Highlights: Increased risk of gestational diabetes in women with schizophrenia. Reduced risk of gestational diabetes in women with anorexia nervosa. Understanding of mechanisms for the relationship could illuminate targets for interventions.